2021
DOI: 10.3390/en14051501
|View full text |Cite
|
Sign up to set email alerts
|

Pd Catalysts Supported on Bamboo-Like Nitrogen-Doped Carbon Nanotubes for Hydrogen Production

Abstract: Bamboo-like nitrogen-doped carbon nanotubes (N-CNTs) were used to synthesize supported palladium catalysts (0.2–2 wt.%) for hydrogen production via gas phase formic acid decomposition. The beneficial role of nitrogen centers of N-CNTs in the formation of active isolated palladium ions and dispersed palladium nanoparticles was demonstrated. It was shown that although the surface layers of N-СNTs are enriched with graphitic nitrogen, palladium first interacts with accessible pyridinic centers of N-СNTs to form s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…All of these states correspond to Pd 2+ species since the same line position is observed for Pd 2+ salts such as acetate or chloride . Earlier studies of catalysts with a low concentration of Pd supported on N-doped carbon showed the presence of similar single-atom Pd 2+ species. ,, …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…All of these states correspond to Pd 2+ species since the same line position is observed for Pd 2+ salts such as acetate or chloride . Earlier studies of catalysts with a low concentration of Pd supported on N-doped carbon showed the presence of similar single-atom Pd 2+ species. ,, …”
Section: Resultsmentioning
confidence: 57%
“…For example, single Pd atoms can form on N-doped carbon and perform better in hydrogen production from gaseous formic acid than Pd atoms in Pd nanoparticles. , During their synthesis, heating of the support with the deposited metal precursor ensures the removal of organic/inorganic ligands and the remaining single Pd atoms bind strongly to the nitrogen sites of the support macroligand. However, traditional wet synthesis is not suitable to give a high concentration of single metal atoms since at a Pd concentration above 0.2–0.3 wt %, the formation of metal nanoparticles occurs and the activity of catalysts decreases. ,, These low concentrations of single-atom Pd sites may indicate that the support sites, which can interact strongly with single metal atoms, have been consumed, allowing Pd to aggregate. At the same time, the synthesis of catalysts with a concentration of single Pd atoms up to 0.4–0.5 wt % supported on g-C 3 N 4 , or polyoxometalate-based metal–organic framework (MOF) was reported.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation with the concentration of pyridinic N atoms was shown. In a recent paper [31], this group demonstrated the same effects for Pd catalysts.…”
mentioning
confidence: 68%
“…Pt has been found to be the best metal for noble metal doping, but it is an expensive noble metal. Therefore, other cheaper but efficient metals have been explored such as Ag, 52 Ni, 53 Ru, 54 Cu, 55 and Pd 56 …”
Section: Application Of Nanoparticles In the Photocatalytic Hydrogen ...mentioning
confidence: 99%
“…Therefore, other cheaper but efficient metals have been explored such as Ag, 52 Ni, 53 Ru, 54 Cu, 55 and Pd. 56 Stability of the photocatalyst plays a key role in the effective biohydrogen production from the wastewater streams. Preethi and Kanmani 57 examined the stability and efficiency of visible light active photocatalysts such as RuO 2 /CuGa 1.6 Fe 0.4 O 4 , ZnFe 2 O 3 , (CdS + ZnS)/Fe 2 O 3 and Ce/TiO 2 for hydrogen production from industrial effluent containing hydrogen sulphide.…”
Section: Application Of Nanoparticles In Dark Fermentative Biohydroge...mentioning
confidence: 99%